An Expanded Palette of Genetically Encoded Ca(2+) Indicators - Zhao, Yongxin (2011)
Engineered fluorescent protein (FP) chimeras that modulate their fluorescence in response to changes in calcium ion (Ca(2+)) concentration are powerful tools for visualizing intracellular signaling activity. However, despite a decade of availability, the palette of single FP-based Ca(2+) indicators has remained limited to a single green hue. We have expanded this palette by developing blue, improved green, and red intensiometric indicators, as well as an emission ratiometric indicator with an 11,000% ratio change. This series enables improved single-color Ca(2+) imaging in neurons and transgenic Caenorhabditis elegans. In HeLa cells, Ca(2+) was imaged in three subcellular compartments, and, in conjunction with a cyan FP–yellow FP–based indicator, Ca(2+) and adenosine 5′-triphosphate were simultaneously imaged. This palette of indicators paints the way to a colorful new era of Ca(2+) imaging.